Exploring management objectives and ecosystem service trade-offs in a semi-arid rangeland basin in southeast Iran (2019)
Ecosystem services are increasingly being included as rangeland management objectives along with grazing, restoration, and conservation. These often conflicting objectives can interact and result in tradeoffs where managing for one ecosystem service (ES) can result in the detriment of another. However, there is scarce information for rangeland systems of central Asia. This study aims to assess tradeoffs interactions between different ES in a semi-arid watershed in Iran with centuries of grazing history. We use field data, the Integrated Valuation of Ecosystem Services model, and spatial analyses to explore the interaction and spatial distribution of rangeland health and its effects on: forage production, water yield, carbon stock, soil retention, and soil formation. We summarized ESs into two bundles: 1. forage production and carbon storage and 2. water yield, soil retention and soil formation. Rangeland health across the study area's three different physiographic regions was determined and ES interaction groups mapped. A classification system of win-win (W-W), win-lose (W-L) and lose-lose (L-L) interactions under current management regimes was also developed using field data and statistical analyses. Findings show a W-L interaction among ESs in the mid-watershed region. Although this region provided the most forage and carbon storage; grazing management practices need to consider the sustainable provision of water yield, soil retention and soil formation. Interaction classes were however W-W in upstream regions where conservation objectives were a priority. Downstream, interaction classes were L-L due to overgrazing and urbanization; thus, restoration and improved management need prioritization. Understanding the spatial distribution of ES interactions can help managers plan for and balance resources with their sustainable supply. © 2018 Elsevier Ltd